Temperature - Quinn, T. J. (Terry J.) (Monographs in physical measurement., 1990)
Temperature, Second Edition gives a comprehensive account of the principles of thermometry over the range 0.5 K to about 3000 K. The book focuses on various topics on the field of thermometry such as the full description of the ITS-90, its practical application and preparation; accounts of total radiation thermometry and acoustic gas thermometry using spherical resonators; and the development of sealed cells for the realization of fixed points. The construction and use of high-temperature platinum resistance thermometers; introduction of the use of gold-platinum thermocouple; and the calibrati.